Terbinafine-loaded branched PLGA-based cationic nanoparticles with modifiable properties - Martiska, Juraj; Snejdrova, Eva; Drastik, Martin; Matysova, Ludmila; Dittrich, Milan; Loskot, Jan; Jilek, Petr (Pharmaceutical development and technology, 2019)
Although the systemic administration of terbinafine is quite well tolerated, topical treatment of the local infections is often preferred. New formulation strategies in topical antifungal therapy represent the polymeric nanoparticles (NPs). We successfully employed the originally synthesized PLGA derivatives of branched architectures of various molar masses, branching ratio, and high number of terminal hydroxyl or carboxyl groups for compounding of terbinafine loaded nanoparticles by nanoprecipitation method. Employing the polymers with tailored properties allowed us to formulate the NPs with desired particle size, loading capacity for drug, mucoadhesive properties, and drug release profile. The hydrophobicity and the polyester concentration revealed the main impact on the NPs size ranging from 100 to 600 nm. The stability of the nanosuspension is demonstrated by zeta potential >25 mV, and polydispersity index values <0.2. We used terbinafine in its less dissolved form of the base to increase the drug loading and delay the release. Cationic surfactant as stabilizer give the NPs high positive surface charge enhancing the adhesion to the mucosal surfaces. All formulations provided prolonged sustained release of terbinafine for several days. Antimicrobial potential has been proven by agar-well diffusion method.
Keywords: Antifungal Agents; velikost částic; kationty; kopolymer kyseliny glykolové a mléčné; Surface-Active Agents; Particle Size; Nanoparticles; Cations; povrchové vlastnosti; Drug Carriers; Solubility; Drug Liberation; rozpustnost; nanočástice; příprava léků; Terbinafine; Administration, Topical; aplikace lokální; Polylactic Acid-Polyglycolic Acid Copolymer; nosiče léků; viskozita; povrchově aktivní látky; Drug Compounding; uvolňování léčiv; terbinafin; antifungální látky; Viscosity; Surface Properties; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions